Genetic characterization of Erwinia amylovora strains by amplified fragment length polymorphism - Rico, A; Ortiz-Barredo, A; Ritter, E; Murillo, J (Journal of applied microbiology, 2004)
Aims:  Erwinia amylovora is one of the most important pathogens of pear and apple and is subject to strict quarantine regulations worldwide, although its patterns of dispersal are largely unknown. Previous attempts to fingerprint E. amylovora strains by molecular techniques have detected very little polymorphism because of the high genetic homogeneity of this bacterium. Our aim was to establish and test a typing method to quantify genetic diversity among strains of this plant pathogen. Methods and Results:  Twenty‐two strains from different hosts and geographical locations were examined by PCR fingerprinting with four primers and by amplified fragment length polymorphism (AFLP) with four selected combinations of primers with a single base extension. PCR fingerprinting revealed little polymorphism producing the same amplification patterns for 17 strains, while the combined AFLP patterns yielded 78 polymorphic bands (34% of total bands) and allowed the differentiation of all but two strains. Clustering of strains in the resulting dendrogram was not correlated with host, year or country of isolation, and questions previous genealogies based on PFGE patterns. Conclusions:  The AFLP technique allowed the detection of an unprecedented number of genetic markers in E. amylovora and proved to be the most useful tool so far for discriminating among strains of this pathogen. The results obtained in this study strongly suggest the occurrence of multiple introductions of the pathogen in Spain and other European countries. Significance and Impact of the Study:  A major limitation in understanding the ecology of fire blight is the lack of typing techniques with a high power of discrimination. This study demonstrates the high resolution and the usefulness of the AFLP technique to differentiate among E. amylovora strains.